Impact of the Static Magnetic Field on Growth, Pigments, Osmolytes, Nitric Oxide, Hydrogen Sulfide, Phenylalanine Ammonia-Lyase Activity, Antioxidant Defense System, and Yield in Lettuce - Arafat Abdel Hamed Abdel Latef; Mona F. A. Dawood; Halimeh Hassanpour; Maryam Rezayian; Nabil A. Younes (Biology, 2020)
Magnetic fields are an unavoidable physical factor affecting living organisms. Lettuce seeds (Lactuca sativa var. cabitat L.) were subjected to various intensities of the static magnetic field (SMF) viz., MF0 (control), SMF1 (0.44 Tesla (T), SMF2 (0.77 T), and SMF3 (1 T) for three exposure times (1, 2, and 3 h). SMF-treated seedlings showed induction in growth parameters and metabolism comparing to control. All photosynthetic pigments were induced markedly under SMF, especially chlorophyll a. SMF at different intensities boosted osmolytes, non-enzymatic antioxidants, and the phenylalanine ammonia-lyase activity over non-magnetized seedlings. Oxidative damage criteria viz., hydrogen peroxide, superoxide radical, and lipid peroxidation, as well as polyphenol oxidase activity, were kept at low values under SMF-treated seeds relative to control, especially SMF2. Electron donors to antioxidant enzymes including nitrate reductase, nitric oxide, and hydrogen sulfide induced via SMF exposure and consequently the activities of superoxide dismutase, glutathione-S-transferases, catalase, and peroxidases family enzymes were also stimulated under SMF, whatever the intensity or the exposure period applied. All these regulations reflected on the enhancement of lettuce yield production which reached 50% over the control at SMF3. Our findings offered that SMF-seed priming is an innovative and low-cost strategy that can improve the growth, bioactive constituents, and yield of lettuce.